2021
DOI: 10.3390/jmse9080861
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Transformation of Sea Surface Gravity Waves at the Shelf of Decreasing Depth

Abstract: This paper reviews the results of the processing of synchronized data on hydrosphere pressure variations and the Earth’s crust deformation in the microseismic range (5–15 s), obtained over the course of numerous experiments, using a coastal laser strainmeter and laser meters of hydrosphere pressure variations installed in various points of the Sea of Japan shelf. Interpreting the results, we have discovered new regularities in the dynamics of surface progressive gravity waves, and their transformation into pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…The relationship between the variations of the main periods of gravity sea waves with dispersion and the Doppler effect, and the variations in wind speed and direction was studied. A thorough study of the dynamics of the main parameters of gravity sea waves in paper [2] revealed new patterns of surface progressive gravity waves and their transformation into primary microseisms, when the waves move on the shelf with decreasing depth. The non-isochronal behavior of progressive waves was established, which manifests itself in a decrease in the gravity waves' periods due to the conversion of a part of their energy into the energy of primary microseisms.…”
Section: Some Results Of the Sea Fluctuation Researchmentioning
confidence: 99%
“…The relationship between the variations of the main periods of gravity sea waves with dispersion and the Doppler effect, and the variations in wind speed and direction was studied. A thorough study of the dynamics of the main parameters of gravity sea waves in paper [2] revealed new patterns of surface progressive gravity waves and their transformation into primary microseisms, when the waves move on the shelf with decreasing depth. The non-isochronal behavior of progressive waves was established, which manifests itself in a decrease in the gravity waves' periods due to the conversion of a part of their energy into the energy of primary microseisms.…”
Section: Some Results Of the Sea Fluctuation Researchmentioning
confidence: 99%
“…The laser meter of hydrosphere pressure variations in water and the 52.5 m “north–south” laser strainmeter at Shultz Cape were operating simultaneously. The waves arriving at Schultz Cape, according to [ 15 ], at depths equal to a half-length of a gravity wave (in our case, with a period of 6.2 s, this was approximately equal to 30 m), began to interact intensively with the bottom, transferring a part of the energy into it, which propagated further into the Earth’s crust in the form of primary microseisms. The 52.5 m laser strainmeter recorded these microseisms.…”
Section: Processing and Analysis Of The Obtained Experimental Datamentioning
confidence: 96%
“…In the spectrum of the ocean-bottom laser seismograph record, a peak with period of about 5.9 s stands out; the same peak can be identified in the record of the laser meter of hydrosphere pressure variations. As the wind wave moved, its period decreased from 6.2 to 5.9 s due to conversion of a part of its energy into the energy of the upper layer of the Earth’s crust, the physics of which are described in [ 15 ].…”
Section: Processing and Analysis Of The Obtained Experimental Datamentioning
confidence: 99%